2006
DOI: 10.1002/jnr.20787
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of TGF‐β in differential astrocyte‐TIMP‐1 regulation: Implications for HIV‐1‐dementia and neuroinflammation

Abstract: Astrocyte production of tissue inhibitor of metalloproteinase (TIMP)-1 is important in central nervous system (CNS) homeostasis and inflammatory diseases such as HIV-1-associated dementia (HAD). TIMPs and matrix metalloproteinases (MMPs) regulate the remodeling of the extracellular matrix. An imbalance between TIMPs and MMPs is associated with many pathologic conditions. Our recently published studies uniquely demonstrate that HAD patients have reduced levels of TIMP-1 in the brain. Astrocyte-TIMP-1 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 64 publications
3
45
0
Order By: Relevance
“…There is evidence that TGF-␤1 levels are increased during immunosuppressive conditions, particularly noteworthy in HIV/AIDS (6). Because PML occurs in the context of JCV reactivation during immunosuppression and is most commonly associated with AIDS, our demonstration of JCV stimulation through a TGF-␤1/MEK axis suggests the importance of TGF-␤1 in pathogenesis.…”
Section: Discussionmentioning
confidence: 76%
“…There is evidence that TGF-␤1 levels are increased during immunosuppressive conditions, particularly noteworthy in HIV/AIDS (6). Because PML occurs in the context of JCV reactivation during immunosuppression and is most commonly associated with AIDS, our demonstration of JCV stimulation through a TGF-␤1/MEK axis suggests the importance of TGF-␤1 in pathogenesis.…”
Section: Discussionmentioning
confidence: 76%
“…MMP-7 production by astrocytes, on the other hand, was drastically increased by IL-1beta stimulation after 24 h, but decreased over time to no significant difference to unstimulated cells by day 14 [16] . As for within the first 24 h of stimulation, IL-1beta did not increase astrocyte secretion of MMP-2 unless simultaneously stimulated with TGF-beta1 or TGFbeta2, while the two TGF-beta isoforms significantly downregulated the IL-1beta-stimulated increase of proMMP-1 [5] . Moreover, IL-1beta stimulation significantly upregulated astrocyte secretion of TGFbeta2 after 7 days and TGF-beta1 after 14 days [5] .…”
Section: Glial Expression Of Timp-1 and Mmp In Had Conditionsmentioning
confidence: 74%
“…As for within the first 24 h of stimulation, IL-1beta did not increase astrocyte secretion of MMP-2 unless simultaneously stimulated with TGF-beta1 or TGFbeta2, while the two TGF-beta isoforms significantly downregulated the IL-1beta-stimulated increase of proMMP-1 [5] . Moreover, IL-1beta stimulation significantly upregulated astrocyte secretion of TGFbeta2 after 7 days and TGF-beta1 after 14 days [5] . These studies demonstrated the intricate network of inflammatory cytokine signaling and feedback to astrocytes and the inherent differences in expression patterns of different MMPs in astrocytes.…”
Section: Glial Expression Of Timp-1 and Mmp In Had Conditionsmentioning
confidence: 74%
See 2 more Smart Citations